DIGITAL TRANSFORMATION AND FIRM PERFORMANCE IN CHINESE MANUFACTURING - Chao Jiang; Paitoon Pimdee; Aukkapong Sukkamart (Veredas do Direito Direito Ambiental e Desenvolvimento Sustentável, 2026)
Digital transformation is becoming a strategic priority for manufacturing firms. However, existing research often treats it as a broad phenomenon, failing to examine differences in the depth of transformation. Therefore, this study introduces the concept of Digital Transformation Degree (DTD) and develops an empirical model based on the TOE framework (Technological, Organizational, Environmental factors). Using survey data from 377 Chinese manufacturing firms and PLS-SEM analysis, the authors examined what drives DTD and how it affects innovation performance (IP) and firm performance (FP). Results show that technological and environmental factors significantly enhance DTD. However, organizational factors do not. Moreover, DTD positively influences both IP and FP, with IP partially mediating the relationship between DTD and FP. These findings highlight that not all TOE dimensions contribute equally to digital transformation, and that innovation is a key pathway through which digital depth creates organizational value. Finally, the study offers manufacturing firms practical guidance, seeking to deepen their digital transformation and convert it into measurable performance gains.
Keywords: Digital Transformation in Industry; Educational Leadership and Innovation; Big Data and Business Intelligence